Multi-Omic Analyses Reveal Bifidogenic Effect and Metabolomic Shifts in Healthy Human Cohort Supplemented With a Prebiotic Dietary Fiber Blend - Kang, Jea Woo; Tang, Xinyu; Walton, Charles J.; Brown, Mark J.; Brewer, Rachel A.; Maddela, Rolando L.; Zheng, Jack Jingyuan; Agus, Joanne K.; Zivkovic, Angela M. (Frontiers in Nutrition, 2022)
Dietary fiber, a nutrient derived mainly from whole grains, vegetables, fruits, and legumes, is known to confer a number of health benefits, yet most Americans consume less than half of the daily recommended amount. Convenience and affordability are key factors determining the ability of individuals to incorporate fiber-rich foods into their diet, and many Americans struggle to access, afford, and prepare foods rich in fiber. The objective of this clinical study was to test the changes in microbial community composition, human metabolomics, and general health markers of a convenient, easy to use prebiotic supplement in generally healthy young participants consuming a diet low in fiber. Twenty healthy adults participated in this randomized, placebo-controlled, double-blind, crossover study which was registered at clinicaltrials.gov as NCT03785860. During the study participants consumed 12 g of a prebiotic fiber supplement and 12 g of placebo daily as a powder mixed with water as part of their habitual diet in randomized order for 4 weeks, with a 4-week washout between treatment arms. Fecal microbial DNA was extracted and sequenced by shallow shotgun sequencing on an Illumina NovaSeq. Plasma metabolites were detected using liquid chromatography–mass spectrometry with untargeted analysis. The phylum Actinobacteria, genus Bifidobacterium, and several Bifidobacterium species (B. bifidum, B. adolescentis, B. breve, B. catenulatum, and B. longum) significantly increased after prebiotic supplementation when compared to the placebo. The abundance of genes associated with the utilization of the prebiotic fiber ingredients (sacA, xfp, xpk) and the production of acetate (poxB, ackA) significantly changed with prebiotic supplementation. Additionally, the abundance of genes associated with the prebiotic utilization (xfp, xpk), acetate production (ackA), and choline to betaine oxidation (gbsB) were significantly correlated with changes in the abundance of the genus Bifidobacterium in the prebiotic group. Plasma concentrations of the bacterially produced metabolite indolepropionate significantly increased. The results of this study demonstrate that an easy to consume, low dose (12 g) of a prebiotic powder taken daily increases the abundance of beneficial bifidobacteria and the production of health-promoting bacteria-derived metabolites in healthy individuals with a habitual low-fiber diet.